EXTRACTING ESSENTIAL OIL FROM FRAGRANT LEMONGRASS PLANTS BY STEAM-HYDRO DISTILLATION METHOD USING MICROWAVE AS A HEATER - Aida Safitri; J. P. Sinaga (Jurnal Sains dan Teknologi Reaksi, 2021)
This research studies the process of extracting citronella oil by the steam-hydro distillation method with microwaves (microwave). In addition, study the effect of temperature (105 ͦ C, 110 ͦ C, 115 ͦ C) and the size of the material enumeration (0.5 cm; 1 cm; 1.5 cm) on the yield of oil produced. This research was conducted by the steam-hydro distillation method. In this method a solvent is added in the form of water to dissolve the oil in the fragrant lemongrass stems and leaves. The resulting steam is condensed and then distillate in the form of a mixture of oil and water is taken after 120 minutes and separated using a separating  funnel. From the results of the study, it was found that the% yield of high citronella oil in the variable size of the enumeration material was 0.5 cm at a temperature of 115 with a yield of 1.92%. The content of Citronella obtained in the oil of this research is 59.28%. The density of lemongrass oil is 0.875. The refractive index value is obtained in the range of 1.46735- 1.46925.Keywords :  Essential Oil, Fragrant, Steam-hydro Distilation, Microwave